(3GdJehjd GdOhdj (B/s - (3Nda, adjM MSfs ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2004)
(3eGgjI GdJehjd GdOhdj hCgejJg(B- (3fTCJg hJWhQg GdJGQjNj(B- (3SYQ GdUQa hGdJehjd GdOhdj(B- (3ejRGf GdeOahYGJ hGdJehjd GdOhdj(B- (3GNJdGd hJhGRf ejRGf GdeOahYGJ(B- (3OhGaY GdJehjd GdOhdj hBKGQg heUGOQg(B- (3CTcGd GdJehjd GdOhdj(B- (3GdefM hGdeSGYOGJ GdQSejI(B- (3fXGe GdfbO hGdJehjd GdOhdj(B- (3GdESJKeGQ GdGLfHj(B- (3hGbY Yed hEOGQI eDSSGJ GdJehjd GdOhdj(B- (3SjGSJgG hCKGQgG(B- (3eTcdGJ GdfXGe GdfbOj GdOhdj(B.s
(3GdeQGLY U(B. 368s
Keywords: (3GdESJKeGQGJs; (3GdEbJUGO GdOhdjs; (3GdJehjd GdOhdjs